Analysis of consumer loyalty based on the aspect of brand image and after sales service - Indah Kusuma Hayati; Sumardjono Sumardjono; Yadi Mulyadi (The Management Journal of Binaniaga, 2020)
Rapid economy development in Indonesia has created tight competitive business. Business people have to try very hard to make their business exist, they are obliged to be able to deal with competitive business keeping the consumers to be loyal. Because consumers are the most important asset for a company. And a company will jeopardize its business if it does not have any consumers. The way how to keep the consumers loyal to the company is thru Brand Image and After Sales Service. This research aims to figure out the extent to which Brand Image and After Sales Service have affected Consumer Loyalty. And Objects of this research are furniture consumers at PT Informa Bogor. Data analysis has applied multiple linear regression analysis, determinant coefficient, F test and T test to test the hypotheses. The result of F test has identified Brand Image and After Sales Service affecting significantly Consumer Loyalty. Partial test has identified independent variables partially affecting significantly Consumer Loyalty. Nevertheless, the contribution of independent variable to the increasing Consumer Loyalty is quite small which is 36.5 %, and the rest has been affected by other factors which are not studied in this research. Keywords: Consumer Loyalty, Brand Image, and After Sales Service